Nanoporous hexagonal TiO2 superstructure as a multifunctional material for energy conversion and storage1. Issue 7 (21st February 2015) - Lee, Eun Joo; Nam, Inho; Yi, Jongheop; Bang, Jin Ho
<x xml:space="preserve">Abstract</x> A new, exotic nanostructured TiO2 is employed as an advanced electrode material for energy applications.